Unveiling the vortex glass phase in the surface and volume of a type-II superconductor - Aragón Sánchez, Jazmín (2019)
Order-disorder transitions between glassy phases are common in nature and yet a comprehensive survey on the entailed structural changes is challenging since the constituents are in the micro-scale. Vortex matter in type-II superconductors is a model system where some of these experimental challenges can be tackled. Samples with point disorder present a glassy transition on increasing the density of vortices. A glassy yet quasi-crystalline phase, the Bragg glass, nucleates at low densities. The vortex glass stable at high densities is expected to be disordered, however its detailed structural properties remained experimentally elusive. Here we show that the vortex glass has large crystallites with in-plane positional displacements growing algebraically and short-range orientational order. Furthermore, the vortex glass has a finite and almost constant correlation length along the direction of vortices, in sharp contrast with strong entanglement. These results are important for the understanding of disorder-driven phase transitions in glassy condensed matter.